Prevalence of overweight misperception and weight control behaviors among normal weight adolescents in the United States - Kathleen S. Talamayan; Andrew E. Springer; Steven H. Kelder; Emmanuel C. Gorospe; Karen A. Joye (The Scientific World Journal, 2006)
Weight perceptions and weight control behaviors have been documented with underweight and overweight adolescents, yet limited information is available on normal weight adolescents. This study investigates the prevalence of overweight misperceptions and weight control behaviors among normal weight adolescents in the U.S. by sociodemographic and geographic characteristics. We examined data from the 2003 Youth Risk Behavior Survey (YRBS). A total of 9,714 normal weight U.S. high school students were included in this study. Outcome measures included self-reported height and weight measurements, overweight misperceptions, and weight control behaviors. Weighted prevalence estimates and odds ratios were computed. There were 16.2% of normal weight students who perceived themselves as overweight. Females (25.3%) were more likely to perceive themselves as overweight than males (6.7%) (p < 0.05). Misperceptions of overweight were highest among white (18.3%) and Hispanic students (15.2%) and lowest among black students (5.8%). Females (16.8%) outnumbered males (6.8%) in practicing at least one unhealthy weight control behavior (use of diet pills, laxatives, and fasting) in the past 30 days. The percentage of students who practiced at least one weight control behavior was similar by ethnicity. There were no significant differences in overweight misperception and weight control behaviors by grade level, geographic region, or metropolitan status. A significant portion of normal weight adolescents misperceive themselves as overweight and are engaging in unhealthy weight control behaviors. These data suggest that obesity prevention programs should address weight misperceptions and the harmful effects of unhealthy weight control methods even among normal weight adolescents.